Advances in paclitaxel combinations for treating cervical cancer. (12th April 2020) - Della Corte, Luigi; Barra, Fabio; Foreste, Virginia; Giampaolino, Pierluigi; Evangelisti, Giulio; Ferrero, Simone; Bifulco, Giuseppe
ABSTRACT: Introduction: Cervical cancer is the fourth common cancer in women worldwide. While, in the past, locally advanced stage disease was treated by pelvic radiotherapy, nowadays the National Cancer Institute strongly recommends chemoradiation protocols. Weekly cisplatin was previously the standard of care in this setting; however, the low response rate and the short median progression-free survival (PFS) of patients have led researchers to investigate combinatory regimens. Area covered: This article is based on literature searches up until April 2019, with current trial registers also analyzed. All data available on this topic has been summarized in this narrative review. Expert opinion: In recent years, it has been demonstrated that cisplatin-based doublets, and in particular, cisplatin plus paclitaxel, are superior to cisplatin as a monotherapy in terms of response rate and progression-free survival of patients with advanced cervical cancer. This double regime combined with bevacizumab is also considered the first-line option for metastatic or recurrent disease. Dose-dense paclitaxel in neo-adjuvant chemotherapy combinations is a promising option in patients with locally advanced cervical cancer. Exploration of novel biological therapies and in vitro combinations based on the use of paclitaxel is warranted.